Piezoelectric ceramic powder for whitening and mineralizing teeth as well as preparation method and application of piezoelectric ceramic powder

By using Ba1-2xSrxCaxTiO3 piezoelectric ceramic powder, reactive oxygen species are produced under ultrasonic/mechanical stimulation, which is used for teeth whitening, and promote mineralization and restoration through Ca and Sr ions, the safety hazards of existing teeth whitening technologies are solved and Dental damage problems have achieved safe and non-destructive teeth whitening and mineralization repair effects.

CN119430910APending Publication Date: 2025-02-14SHANGHAI XUHUI DISTRICT DENTAL HOSPITAL (SHANGHAI XUHUI DISTRICT DENTAL DISEASE CONTROL & PREVENTION INSTITUTE)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411587857.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing dental whitening technology has safety hazards and potential dental damage problems, and it is difficult to achieve long-term and non-destructive whitening effects.

Method used

A piezoelectric ceramic powder with the chemical formula of Ba1-2xSrxCaxTiO3 is used. This powder produces reactive oxygen species under ultrasonic/mechanical force stimulation, which is used for teeth whitening and promotes tooth mineralization and repair through Ca and Sr ions.

Benefits of technology

It achieves the dual effects of teeth whitening and mineralization restoration, avoids tooth damage, and has good biocompatibility and long-term effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430910A_ABST
    Figure CN119430910A_ABST
Patent Text Reader

Abstract

The invention discloses piezoelectric ceramic powder for tooth whitening and mineralization and a preparation method thereof, the chemical formula of the piezoelectric ceramic powder for tooth whitening and mineralization is Ba (1-2x) SrxCaxTiO3, and the element ratio of Ba: Sr: Ca: Ti: O is (1-2x): x: x: 1: 3, the preparation method comprises the following steps: preparing a precursor solution by adopting a sol-gel method, preparing a homogenized solution into dry sol after aging and drying, and then preparing the piezoelectric ceramic powder through high-temperature heat treatment. The tooth cleaning agent can efficiently respond to external ultrasonic stimulation to generate active oxygen, stains on the surfaces of teeth can be effectively decomposed and removed, the remineralization process of the surfaces of the teeth can be promoted, and therefore the hardness and the anti-caries capacity of the teeth are enhanced. Meanwhile, the material shows excellent biocompatibility, and the safety of the material in an oral environment and the feasibility of long-term use of the material are ensured. The invention can provide a convenient and long-acting method for promoting tooth whitening and mineralization repair, and the problem of tooth damage caused by the use of excessive bleaching reagents and the like during tooth whitening is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical materials, and in particular to a piezoelectric ceramic powder for teeth whitening and mineralization, and a preparation method and application thereof. Background Art

[0002] Teeth whitening is an important part of modern dental beauty. External stains and endogenous color changes jointly affect the change of tooth color. Among them, the adsorption characteristics of enamel and dentin for pigments determine the intrinsic color of teeth. The adhesion of stains caused by smoking, food intake (dark fruits, coffee, tea and vinegar, etc.) is another important reason for tooth color change. Colored groups aggregate and adhere to the tooth surface through interactions such as electrostatic force, van der Waals force and hydrogen bond. Carbohydrates and amino compounds in food can also cause Maillard reaction, leading to the formation of melanoidins, causing tooth discoloration.

[0003] Therefore, in order to meet the demand for whiter teeth, a variety of tooth whitening solutions have been developed. Among them, daily brushing with toothpaste containing abrasives is a simple and safe method of home tooth whitening, but its effect is very limited because only external stains on the tooth surface can be removed by the polishing effect of abrasives (such as aluminum hydroxide). In contrast, chemical bleaching using hydrogen peroxide and / or carbamide peroxide is more effective because the reactive oxygen species (ROS) released when they decompose can penetrate into the enamel and trigger the oxidative degradation of organic pigment molecules. In addition to the high-concentration (e.g., 30-40%) peroxide bleaching gels widely used clinically, there are also some over-the-counter products containing low-concentration (e.g., 3-12%) peroxides that can achieve good whitening effects at home. However, these peroxides may cause serious side effects to teeth and surrounding gingival tissues due to the violent release of ROS, such as enamel damage, increased tooth sensitivity, and gingival irritation. Therefore, we are in urgent need of a safer, more convenient, and more durable tooth whitening solution.

[0004] As a non-invasive whitening solution, photocatalysis has the potential to achieve tooth whitening by utilizing metal or metal oxide (e.g., titanium dioxide) nanoparticles to generate ROS under light excitation. However, traditional photocatalytic methods are limited by the safety hazards of short-wavelength light sources, including phototoxicity and photosensitivity issues, which greatly restricts the popularity of their home applications. Recently, an innovative solution based on the piezoelectric effect of polarized barium titanate (BaTiO3) nanoparticles has been proposed, which cleverly integrates the whitening process into daily brushing habits, showing the advantages of convenience and non-destructiveness. Driven by the mechanical vibration of an electric toothbrush, barium titanate nanoparticles can continuously provide free charges to water molecules or oxygen, promote redox reactions, and generate on-site free radicals such as hydroxyl radicals (·OH) and superoxide anions (·O 2-) and other powerful cleaning active oxygen, effectively removing stains on the tooth surface. Compared with traditional peroxide bleaching methods, this piezoelectric catalytic whitening technology is not only more suitable for home use, but also avoids potential damage to teeth. However, despite its significant whitening effect, barium titanate-based whitening agents can easily cause irreversible damage to tooth enamel. In view of the current market's urgent need for safe, efficient and non-destructive tooth whitening products, as well as the limitations of existing technologies in terms of biosafety, catalytic activity and single functionality, it is particularly necessary to conduct in-depth research on a piezoelectric material that combines tooth whitening and mineralization repair functions. Summary of the invention

[0005] The purpose of the present invention is to provide a convenient and long-lasting piezoelectric ceramic powder for promoting tooth whitening and mineralization repair, as well as a preparation method and application thereof. The ceramic powder generates active oxygen for tooth whitening under the stimulation of ultrasonic / mechanical force, and promotes mineralization repair of tooth surface, thereby avoiding tooth damage caused by excessive use of bleaching agents during tooth whitening.

[0006] A piezoelectric ceramic powder for teeth whitening and mineralization, the chemical formula of which is Ba 1-2x Sr x Ca x TiO3, its element ratio is Ba:Sr:Ca:Ti:O=(1-2x):x:x:1:3.

[0007] The range of the amount of x is: 0.01 <x<0.5。

[0008] The x=0.05, and the element ratio is Ba:Sr:Ca:Ti:O=0.9:0.05:0.05:1:3.

[0009] The method for preparing the piezoelectric ceramic powder for teeth whitening and mineralization comprises the following steps:

[0010] (1) According to the chemical formula Ba 1-2x Sr x Ca x TiO3, barium acetate (purity 99%), calcium acetate (purity 99%), and strontium acetate (purity 98%) were weighed and dissolved in acetic acid according to a molar ratio of (1-2x):x:x, and then mixed and stirred at 60-90°C for 30 minutes, and then naturally cooled to room temperature to obtain solution A;

[0011] (2) dissolving tetrabutyl titanate in 1 mL of acetylacetone and 9 mL of ethylene glycol methyl ether according to a stoichiometric ratio to form a homogenized solution B;

[0012] (3) mixing solutions A and B for 5 h and aging for 24 to 96 h to form a homogenized solution C, which is then dried at 90 to 150 °C to form a xerosol;

[0013] (4) The dry sol was heat treated at 600-1200°C (heating rate 5°C / min) for 2 h to form BaSrCaTiO3-based ceramic powder (BSCT).

[0014] In step (1), x=0.05 and the stirring temperature is 70°C.

[0015] In the step (3), the aging time is 72 hours and the drying temperature is 120°C.

[0016] The heat treatment temperature in step (4) is 900°C.

[0017] The application of the piezoelectric ceramic powder for teeth whitening and mineralization is the application in teeth whitening and promoting the mineralization and repair of tooth surface.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The piezoelectric ceramic powder of the present invention can efficiently respond to external ultrasonic stimulation and generate active oxygen (such as superoxide anions, hydrogen peroxide, etc.) with strong oxidizing ability. These active oxygen can not only effectively decompose and remove stains on the surface of teeth, such as coffee stains, tea stains, smoke stains, etc., but also have good piezoelectric effect and can be used for teeth whitening.

[0020] (2) The piezoelectric ceramic powder of the present invention contains Ca and Sr ions, which can promote the mineralization and repair of the tooth surface, thereby enhancing the hardness and anti-caries ability of the tooth.

[0021] (3) The piezoelectric ceramic powder described in the present invention has good biocompatibility, ensuring its safety in the oral environment and feasibility of long-term use. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The transmission electron microscope photo of the BSCT powder prepared in Example 1 and the element distribution diagram of the BSCT powder indicate that a powder with a size of about 80 nm was successfully prepared, and Ti, Ba, Ca, O and Sr elements were evenly distributed in the powder.

[0023] Figure 2 This is the PFM test result of the BSCT powder prepared in Example 1, which shows that the powder has a piezoelectric effect (Height: height; Amplitude: amplitude; Phase: phase).

[0024] Figure 3 This is the ESR result of the BSCT powder prepared in Example 1 measured under ultrasonic stimulation conditions, indicating that the powder can produce active oxygen in response to ultrasonic stimulation (Magnetic field: magnetic field; Intensity: intensity).

[0025] Figure 4 The results of the degradation experiment of indigo carmine dye solution by BSCT powder prepared in Example 1 under ultrasonic stimulation indicate that the powder can respond to ultrasonic stimulation to degrade indigo carmine dye solution (Wavelength: wavelength; Absorbance: absorption intensity).

[0026] Figure 5 The cleaning effect of the BSCT powder prepared in Example 1 on tooth surface stains under simulated tooth brushing conditions indicates that the powder can effectively remove tooth surface stains and achieve a tooth whitening effect.

[0027] Figure 6 The BSCT powder prepared in Example 1 has a remineralization effect on the tooth surface in the mineralization experiment. The SEM results show that obvious crystalline particle deposition can be observed on the enamel and dentin surfaces of the teeth treated with BSCT powder. The XRD results show the appearance of a weak peak belonging to hydroxyapatite (Enamel: enamel; Dentin: dentin; Normal Tooth: normal tooth; Demineralized Tooth: demineralized tooth).

[0028] Figure 7 The results of live and dead cell staining of the BSCT powder prepared in Example 1 when used to culture human gingival fibroblasts indicate that the powder has good biocompatibility (Live: live cell staining; Dead: dead cell staining). DETAILED DESCRIPTION

[0029] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0030] The present invention relates to a BaSrCaTiO3-based piezoelectric ceramic powder (named "BSCT") and its preparation method and application. The present invention adopts a sol-gel method to prepare a precursor solution, and then prepares a dry sol by aging and drying, and finally obtains a piezoelectric ceramic powder after heat treatment. The piezoelectric powder can generate active oxygen under mechanical stress and ultrasonic stimulation, which can be used for teeth whitening to remove stains on the tooth surface and promote mineralization of the tooth surface.

[0031] The following further exemplifies the present invention in detail. It should be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of the present invention. The specific process parameters of the following examples are only examples in a suitable range, and those skilled in the art can make selections within a suitable range through the description of this article, but are not limited to the specific numerical values ​​​​exemplified below. Unless otherwise defined or specified, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equal to the recorded content can be applied to the method of the present invention.

[0032] Example 1

[0033] Sol-gel preparation of Ba 0.9 Sr 0.05 Ca 0.05 TiO3 powder: (1) Dissolve barium acetate (purity 99%), strontium acetate (purity 99%), and calcium acetate (purity 98%) in 30 mL of acetic acid according to a stoichiometric ratio, stir magnetically at 70°C for 30 min until completely dissolved, and cool to room temperature to form a homogenized solution A; (2) Dissolve tetrabutyl titanate in 1 mL of acetylacetone and 9 mL of ethylene glycol methyl ether according to a stoichiometric ratio to form a homogenized solution B; (3) Mix solutions A and B and stir for 5 h, and age for 72 h to form a homogenized solution C; (4) Dry the homogenized solution C at 120°C for 24 h to form a xerosol; (5) Heat treat the xerosol at 900°C (heating rate 5°C / min) for 2 h to form a BaSrCaTiO3-based ceramic powder, named BSCT.

[0034] like Figure 1 As shown, the prepared powder has a particle size of about 80 nm, and the powder contains Ti, Ba, Ca, O, and Sr elements, which are evenly distributed.

[0035] like Figure 2 As shown, the amplitude diagram and phase diagram of the prepared powder show obvious contrast changes, and have obvious butterfly displacement-voltage curve and phase change curve, indicating that the polarization direction of the powder changes under voltage changes and has hysteresis, indicating that the powder has piezoelectric effect.

[0036] Example 2

[0037] DMPO was used as a capture agent to mix BSCT powder with methanol reaction system to detect O 2- DMPO was used as a trapping agent and BSCT powder was added to the pure water reaction system to detect ·OH. Before collecting the signal, the mixed liquid was treated in an ultrasonic instrument at 1W power for 2 minutes.

[0038] like Figure 3 As shown in the figure, after ultrasonic treatment, the BSCT powder can capture obvious superoxide radical peaks and hydroxyl radical peaks, indicating that BSCT powder can generate ·O 2- and OH.

[0039] Example 3

[0040] Dissolve and prepare a 0.1 mg / mL indigo carmine solution, and divide it into two groups. One group adds 1 mg / mL BSCT powder, and the control group does not add powder. The ultrasonic power is set to 2w, and the ultrasonic treatment is performed for 40 minutes. Every 10 minutes, 100uL of the solution is collected and cooled to room temperature. Take pictures and detect the absorbance change curve of the solution at 450-750nm.

[0041] like Figure 4 As shown in the figure, with the extension of ultrasonic treatment time, the blue color of the indigo carmine solution in the piezoelectric powder group gradually faded, and the absorbance intensity at 600nm weakened with time. There was no obvious change in the color and absorbance change curves of the control group solution.

[0042] Example 4

[0043] Healthy teeth without obvious stains from orthodontic patients were collected, soaked in a solution containing black tea and coffee for 48 hours, then taken out and rinsed with normal saline. A 1 mg / mL BSCT piezoelectric ceramic powder suspension was prepared with normal saline, and the suspension was used with an electric toothbrush to clean the teeth. The control group was cleaned with normal saline. A colorimeter was used to measure the color value changes in the root area of ​​the teeth, where the ΔE value was calculated according to the following formula:

[0044] Among them, L, a, and b values ​​are the light and dark values, red and green values, and blue and green values ​​of the measured point respectively.

[0045] like Figure 5 As shown in the figure, with the extension of simulated toothbrushing time, the color of tooth surface stains in the BSCT group gradually faded from dark brown, and the L value and a value were close to the untreated values ​​after 12 hours of treatment, and the ΔE value was significantly higher than that of the control group, indicating that after powder treatment, the color of teeth changed significantly and was close to the color before treatment.

[0046] Example 5

[0047] Healthy teeth without obvious stains from orthodontic patients were collected, and the tooth slices were prepared by longitudinal section. The tooth slices were soaked in demineralization solution for 48 hours and then taken out and rinsed with normal saline. The tooth slices were divided into two groups. The tooth slices in the BSCT group were soaked in 1mg / mL BSCT powder suspension prepared with artificial saliva, and the tooth slices in the powder-free group were soaked in artificial saliva. The two groups of tooth slices were placed on a 37℃ constant temperature shaker, and the solution was changed every day. After 7 days, they were taken out for SEM observation.

[0048] like Figure 6 As shown in the figure, the SEM results show that obvious crystalline particle deposition can be observed on the enamel and dentin surfaces of teeth treated with BSCT powder. The XRD results show that there is a weak peak belonging to hydroxyapatite, indicating that BSCT powder contributes to the mineralization of the tooth surface.

[0049] Example 6

[0050] Healthy gingival tissue of patients was collected to isolate human gingival fibroblasts, and the culture medium used was DMEM high-glucose medium (supplemented with 15% FBS and 1% double antibody). DMEM high-glucose medium with 1mg / mL BSCT powder was prepared, and the extract was collected after 48h. When performing biocompatibility testing, cells in the control group were cultured with DMEM high-glucose medium, cells in the BSCT group were cultured with extract, and cells in the H2O2 group were cultured with DMEM high-glucose medium containing 3% H2O2. After 48h, Live / Dead cell staining reagent was used for cell live and dead staining.

[0051] like Figure 7 As shown, with or without the addition of powder, obvious green fluorescence marking living cells can be observed, and red fluorescence is rarely observed, indicating that the powder has good biocompatibility. The red fluorescence intensity of the H2O2 group is significantly enhanced, indicating that a large number of cells in this group have died.

[0052] The present invention provides a convenient and long-lasting method for promoting teeth whitening and mineralization repair, thereby avoiding tooth damage caused by excessive use of bleaching agents during teeth whitening. This discovery not only broadens the application field of piezoelectric ceramic materials, but also provides a new solution for oral health care.

Claims

1. A piezoelectric ceramic powder for teeth whitening and mineralization, characterized in that: Its chemical formula is Ba 1-2x Sr x Ca x TiO3, The element ratio is Ba:Sr:Ca:Ti:O = (1 - 2x):x:x:1:

3.

2. The piezoelectric ceramic powder for teeth whitening and mineralization according to claim 1, characterized in that: The amount range of the said x is: 0.01 < x < 0.

5.

3. The piezoelectric ceramic powder for teeth whitening and mineralization according to claim 1 or 2, characterized in that: The amount range of the said x is: 0.01 < x < 0.

5. The said x = 0.05, and the element ratio is Ba:Sr:Ca:Ti:O = 0.9:0.05:0.05:1:

3.

4. A method for preparing a piezoelectric ceramic powder for teeth whitening and mineralization as claimed in claim 1 or 2, characterized in that: It includes the following steps: (1) According to the chemical formula Ba 1-2x Sr x Ca x TiO3, barium acetate (purity 99%), calcium acetate (purity 99%), and strontium acetate (purity 98%) were weighed and dissolved in acetic acid according to a molar ratio of (1-2x):x:x, and then mixed and stirred at 60-90°C for 30 minutes, and then naturally cooled to room temperature to obtain solution A; (2) Dissolve tetrabutyl titanate in 1 mL of acetylacetone and 9 mL of ethylene glycol methyl ether according to the stoichiometric ratio to form a homogenized solution B; (3) Mix and stir solutions A and B for 5 h, and age for 24 - 96 h to form a homogenized solution C, and then dry at a temperature of 90 - 150 °C to form a dry sol; (4) Heat-treat the dry sol at 600 - 1200 °C (heating rate 5 °C / min) for 2 h to form BaSrCaTiO3-based ceramic powder (BSCT).

5. The method for preparing piezoelectric ceramic powder for teeth whitening and mineralization according to claim 4, characterized in that: In the said step (1), x = 0.05, and the stirring temperature is 70 °C.

6. The method for preparing piezoelectric ceramic powder for teeth whitening and mineralization according to claim 4, characterized in that: In the said step (3), the aging time is 72 hours, and the drying temperature is 120 °C.

7. The method for preparing piezoelectric ceramic powder for teeth whitening and mineralization according to claim 4, characterized in that: In the said step (4), the heat-treatment temperature is 900 °C.

8. An application of the piezoelectric ceramic powder for teeth whitening and mineralization as claimed in claim 1, characterized in that: It is for the application in tooth whitening and promoting the mineralization repair of the tooth surface.

Citation Information

Patent Citations

  • Environment-coordinating method for preparing titanate piezoelectric ceramic powder

    CN102898147A

  • Tooth whitening product containing piezoelectric material

    CN110464674A

  • BaTiO3 composite piezoelectric hydrogel as well as preparation method and application thereof

    CN117883632A

  • Preparation method of high-performance barium titanate lead-free piezoelectric ceramic

    CN118373681A

  • Perovskite titanium-type composite oxide particle and productionprocess thereof

    US20020150531A1